Derivative of Arctan
Before going to see what is the derivative of arctan, let us see some facts about arctan. Arctan (or) tan^{1} is the inverse function of the tangent function. i.e., If y = tan^{1}x then tan y = x. Also, we know that if f and f^{1} are inverse functions of each other then f(f^{1}(x)) = f^{1}(f(x)) = x. From this, tan(arctan x) = arctan(tan x) = x in the respective domains. We use these facts to find the derivative of arctan x.
Let us see the formula of derivative of arctan along with proof and few solved examples.
1.  What Is Derivative of Arctan? 
2.  Derivative of Arctan Proof by Chain Rule 
3.  Derivative of Arctan Proof by First Principle 
4.  FAQs on Derivative of Arctan 
What Is Derivative of Arctan?
The derivative of arctan x is represented by d/dx(arctan x) (or) d/dx(tan^{1}x) (or) (arctan x)' (or) (tan^{1}x)'. Its value is 1/(1+x^{2}). We are going to prove it in two methods in the upcoming sections. The two methods are
 Using the chain rule
 Using the first principle
Derivative of Arctan x Formula
The derivative of the arctangent function is,
 d/dx(arctan x) = 1/(1+x^{2}) (OR)
 d/dx(tan^{1}x) = 1/(1+x^{2})
We are going to prove this formula now in the next sections.
Derivative of Arctan Proof by Chain Rule
We find the derivative of arctan using the chain rule. For this, assume that y = arctan x. Taking tan on both sides,
tan y = tan (arctan x)
By the definition of inverse function, tan (arctan x) = x. So the above equation becomes,
tan y = x ... (1)
Differentiating both sides with respect to x,
d/dx (tan y) = d/dx(x)
We have d/dx (tan x) = sec^{2}x. Also, by chain rule,
sec^{2}y · dy/dx = 1
dy/dx = 1/sec^{2}y
Using one of the trigonometric identities, sec^{2}y = 1 + tan^{2}y.
dy/dx = 1/(1 + tan^{2}y)
dy/dx = 1/(1 + x^{2}) (from (1))
Substituting y = arctan x back here,
d/dx (arctan x) = 1/(1 + x^{2})
Hence proved.
Derivative of Arctan Proof by First Principle
The derivative of a function f(x) by the first principle is given by the limit, f'(x) = limₕ→₀ [f(x + h)  f(x)] / h. To find the derivative of arctan x, assume that f(x) = arctan x. Then f(x + h) = arctan (x + h). Substituting these values in the above limit,
f'(x) = limₕ→₀ [arctan (x + h)  arctan x] / h
By inverse trigonometric formulas, We have arctan x  arctan y = arctan [(x  y)/(1 + xy)]. Apply this, we get
f'(x) = limₕ→₀ [arctan[(x + h  x)/(1 + (x + h) x)] ] / h
= limₕ→₀ (1/h) [arctan [ h / (1 + x^{2} + hx) ] ]
We have arctan x = x  x^{3}/3 + x^{5}/5  ... Using this, we get
f'(x) = limₕ→₀ (1/h) [ h / (1 + x^{2} + hx)  [h / (1 + x^{2} + hx)]^{3} / 3 + [h / (1 + x^{2} + hx)]^{5 }/ 5  ....]
= limₕ→₀ (1/h) [ h / (1 + x^{2} + hx)  [h^{3} / [3(1 + x^{2} + hx)^{3}] + [h^{5} / [5(1 + x^{2} + hx)^{5}]^{ }  ....]
Distributing (1/h),
f'(x) = limₕ→₀ [ 1 / (1 + x^{2} + hx)  [h^{2} / [3(1 + x^{2} + hx)^{3}] + [h^{4} / [5(1 + x^{2} + hx)^{5}]^{ }  ....]
Applying the limit h→0,
f'(x) = 1 / (1 + x^{2 }+ 0)  0 + 0  ...
f'(x) = 1/(1 + x^{2})
Hence proved.
Related Articles:
Here are some topics that are related to the derivative of arctan x.
Solved Examples Using Derivative of Arctan x

Example 1: Find the derivative of y = x arctan x.
Solution:
The given function is, y = x arctan x.
By product rule, its derivative is
y' = x · d/dx (arctan x) + arctan x · d/dx(x)
= x [1/(1+x^{2})] + arctan x (1)
= x/(1+x^{2}) + arctan x
Answer: The derivative of the given function is x/(1+x^{2}) + arctan x.

Example 2: Find the derivative of y = arctan (1/x).
Solution:
Let f(x) = arctan (1/x).
We know that d/dx (arctan x) = 1/(1+x^{2}).
Also, by chain rule,
y' = 1/(1 + (1/x)^{2}) · d/dx (1/x)
= 1/ (1 + (1/x^{2})) · (1/x^{2})
= x^{2}/(x^{2} + 1) · (1/x^{2})
= (1) / (x^{2} + 1)
Answer: The derivative of the given function is (1) / (x^{2} + 1).

Example 3: Find the derivative of y = tan^{1}(1 + x^{2}).
Solution:
Let f(x) = tan^{1}(1 + x^{2}).
We know that d/dx (tan^{1} x) = 1/(1+x^{2}).
Also, by chain rule,
y' = 1 / [1 + (1+x^{2})^{2}] · d/dx (1 + x^{2})
= 1 / [1 + x^{4 }+ 2x^{2} + 1] · (2x)
= (2x) / [x^{4 }+ 2x^{2} + 2]
Answer: The derivative of the given function is (2x) / [x^{4 }+ 2x^{2} + 2].
FAQs on Derivative of Arctan
What is Derivative of Arctan?
The derivative of arctan x is 1/(1+x^{2}). i.e., d/dx(arctan x) = 1/(1+x^{2}). This also can be written as d/dx(tan^{1}x) = 1/(1+x^{2}).
How to Prove Derivative of Arctan Formula?
To derive the derivative of arctan, assume that y = arctan x then tan y = x. Differentiating both sides with respect to y, then sec^{2}y = dx/dy. Taking reciprocal on both sides, dy/dx = 1/(sec^{2}y) = 1/(1+tan^{2}y) = 1/(1+x^{2}).
What is the Derivative of Arctan x/2?
We have the derivative of arctan x to be 1/(1 + x^{2}). By using this and chain rule, the d/dx(arctan x/2) = 1/(1+(x/2)^{2}) d/dx (x/2) = 1/(1 + (x^{2}/4)) · (1/2) = [4/(4 + x^{2})] · (1/2) = 2/(4 + x^{2}).
What is the Derivative of Arctan √x?
We know that the derivative of arctan x to be 1/(1 + x^{2}). By using this formula and chain rule, the d/dx(arctan √x) = 1/(1+(√x)^{2}) d/dx (√x) = 1/(1 + x) · (1/2√x) = 1/(2√x(1+x)).
Is Arctan the Derivative of Tan?
No, the derivative of arctan is NOT tan. The derivative of arctan x is 1/(1 + x^{2}).
What is the Difference Between the Derivatives of Tan x and Arctan x?
The derivative of tan x is sec^{2}x whereas the derivative of arctan x is 1/(1+x^{2}).
What is the Derivative of Arctan x/a?
The derivative of arctan x to be 1/(1 + x^{2}). By using this and chain rule, the d/dx(arctan x/a) = 1/(1+(x/a)^{2}) d/dx (x/a) = 1/(1 + (x^{2}/a^{2})) · (1/a) = [a^{2}/(a^{2} + x^{2})] · (1/a) = a/(a^{2} + x^{2}).
visual curriculum